Reading leadership through Hegel's master/slave dialectic: Towards a theory of the powerlessness of the powerful. (November 2014) - Harding, Nancy
This paper develops a theory of the subjectivity of the leader through the philosophical lens of Hegel's master/slave dialectic and its recent interpretation by the philosopher Judith Butler. This is used to analyse the working life history of a man who rose from poverty to a leadership position in a large company and eventually to running his own successful business. Hegel's dialectic is foundational to much Western thought, but in this paper, I rashly update it by inserting a leader in between the master, whose approval the leader needs if s/he is to sustain self-hood, and the follower, who becomes a tool that the leader uses when trying to gain that elusive approval. The analysis follows the structure of Butler's reading of the Dialectic and develops understanding of the norms that govern how leaders should act and the persons they should be. Hard work has become for leaders an ethical endeavour, but they grieve the sacrifice of leisure. They enjoy a frisson of erotic pleasure at their power over others but feel guilt as a result. They must prove their leadership skills by ensuring their followers are perfect employees but at the same time must prove their followers are poor workers who need their continued leadership. This leads to the conclusion that the leader is someone who is both powerful and powerless. This analysis is intended not to demonize leaders, but to show the harm that follows the emphasis on leadership as a desirable and necessary organizational function.